2007
DOI: 10.1001/archpsyc.64.11.1251
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Disorders and Sex Offending in a Danish Birth Cohort

Abstract: Context: Psychotic disorders are associated with an increased risk of aggressive behavior and violent crime. Whether there is also an association with sex offending is unknown.Objectives: To estimate the lifetime prevalence of arrests for sexual offenses (with and without physical aggression) among men and women with psychotic disorders, the moderating effects of comorbid personality disorders and substance use disorders, and the prevalence rates for 4 specific psychotic disorders. Design:We examined official … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 51 publications
1
39
1
3
Order By: Relevance
“…The fact that the percentage encountered was lower than expected may reflect a difficulty in establishing or describing such a diagnosis, or it may reveal that most of the experts did not attribute great importance to that diagnosis. Indeed, the numbers are far lower than those found by Alden et al 37 and others. 20,22,30 Fazel & Rongquin, 28 in a meta-analysis of 27 studies, compared the risk of criminal recidivism among a total 3,511 psychotic individuals, 5,446 with mental illness but not psychotic, and 71,552 with no mental illness.…”
Section: 36contrasting
confidence: 59%
See 2 more Smart Citations
“…The fact that the percentage encountered was lower than expected may reflect a difficulty in establishing or describing such a diagnosis, or it may reveal that most of the experts did not attribute great importance to that diagnosis. Indeed, the numbers are far lower than those found by Alden et al 37 and others. 20,22,30 Fazel & Rongquin, 28 in a meta-analysis of 27 studies, compared the risk of criminal recidivism among a total 3,511 psychotic individuals, 5,446 with mental illness but not psychotic, and 71,552 with no mental illness.…”
Section: 36contrasting
confidence: 59%
“…There is solid evidence in scientific studies, including systematic reviews and meta-analyses, that proves that mental illness is far from being the most important factor in assessing risk of violence, and may not even be an isolated factor. 1,20,21,28,30,33,34,37 Bonta et al 30 conducted a meta-analysis to evaluate the main predictors of criminal recidivism in individuals with and without mental illness. A total of 64 studies with 74 predictors were analyzed.…”
Section: 36mentioning
confidence: 99%
See 1 more Smart Citation
“…In this review study we found several factors associated to, as well as motivators of sexual offences, also mentioned as important for recidivism of these offences, according with these instruments cited above: presence of serious mental disorders such as schizophrenia [10][11][12][13][14][15]18,34 , bipolar disorder 10,14,17,18,20,39 , existence of sexual deviants 10,13,15,20,21,33,39 , presence of personality disorders 14,18,24,34 , problems associated with the use of alcohol and/or substances 6,14,15,17,18,20,27 , seriousness of sexual aggression [10][11][12][13][14][15]18,20,21,[26][27][28][37][38][39] , record of abuse in childhood 1...…”
Section: Discussionmentioning
confidence: 99%
“…A study by Alden et al 14 , examined the data of individuals born in Denmark, between the years of 1944 and 1947, through official records, who were accompanied till the year 1991. The final sample consisted of 173.559 men.…”
Section: Sexual Offences and Schizophrenia And Other Psychotic Disordersmentioning
confidence: 99%